Political Turmoil and Informal Entrepreneurship: Uncovering Drivers of Resilience in Developing Countries - Kusuma Dewi, Rismaida; Qurrota A'yun, Annisa (Inovasi Analisis Data, 2025)
Purpose: This paper provides evidence on how external institutional contexts and internal cognitive dimensions are associated with the engagement in informal entrepreneurship in emerging markets.Method: Methods A quantitative study was used in this study with structured questionnaires and analysis using SPSS to 438 subjects in Indonesia.Findings: The severity of political contestation level, decomposition of formal economy access, poor institutional governance and community social capital increase informal entrepreneurship. Additionally, a resilience-based entrepreneurial mindset (REM) has a significant moderating and enhancing effect on the relationships.Novelty: The research adds to the literature on entrepreneurship by offering REM as a new cognitive moderator that serves to neutralise institutional adversity and stimulate entrepreneurial engagement, dovetailing institutional theory and entrepreneurial cognition.Implications: The study contributes to theory development by highlighting psychological resilience in institutional void environments, while providing practitio- ners with guidance to facilitate adaptive entrepreneurship in vulnerable domains. More broadly, it offers a portable framework for interpreting the informal entrepreneurial ecosystem in a context of uncertainty and institutional frailty.